I still dream about you : a novel - Flagg, Fannie (New York : Random House, 2010)
Maggie Fortenberry learns valuable lessons about the nature of friendship, the challenges of modern life, and the dangers of impossible dreams as she struggles to keep Red Mountain Realty afloat and bury the heartbreaking secrets of her past.
Keywords: Women real estate agents -- Fiction; City and town life -- Fiction; Alabama -- Fiction; Humorous fiction; Mystery fiction